E-learning as a tool to impart knowledge of surgical procedures in the undergraduate medical teaching - K., Poomalar G.; S., Ilamathi; K., Nivedita; A., Bupathy; M., Jayasree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: E-learning is in a budding stage in developing countries. As present-day students are gadget-friendly, introducing a surgical e-learning module may create interest and help in understanding the surgeries easily. This study aimed to determine the effectiveness of E-learning in improving the knowledge component of surgical procedures for undergraduate students and to analyze students’ feedback regarding its usefulness. Methods: This quasi-experimental study was conducted among 67 final-year MBBS students, who had completed 1 week of operation theatre (OT) posting in obstetrics and gynecology. Recording of videos for must-know surgeries in gynecology was done. Video editing and audio description of surgical steps were done. A YouTube channel was created and surgical videos were uploaded. Links to 2 surgical videos and additional teaching materials were uploaded to the college learning management system daily for 2 consecutive weeks. A telegram group was formed for posting questions daily. Pre-test and post-test were conducted and the results were analyzed. Results: The mean marks obtained in the pre-test were 6.567±1.9 and the post-test was 15.22±2.5 (Paired t test p=0.0001). Students mentioned that combining OT posting with an e-learning module helped them to build their knowledge of surgical procedures. Telegram quizzes helped them to increase their understanding of surgeries. 34 students wanted e-learning module to be conducted on other topics also. Conclusions: E-learning is highly effective in improving knowledge component of surgical procedures for undergraduate students. E-learning can be made more effective by adding formative assessment. Combining surgical e-learning module with operation theatre posting can enhance knowledge and understanding.